Exploring the use of blockchain in resource‐constrained fog computing environments. (29th November 2022) - Sánchez‐de la Rosa, Miguel; Núñez‐Gómez, Carlos; Caminero, M. Blanca; Carrión, Carmen
Summary: Fog computing has become a complementary technology to cloud computing and addresses some of the cloud computing threats such as the response time and network bandwidth demand. Fog computing successes processing data and storing data near to the edge, and usually is combined with container virtualization to provide hardware isolation. Empowered by these capabilities, numerous Internet of Things (IoT) applications are developed as virtualized instances on resource‐constrained fog nodes such as single‐board computers (SBC). In addition, blockchain has emerged as a key technology that is transforming the way we share information. Blockchain technology represents a decentralised, distributed, and immutable database ledger and is a potential solution for the distributed ecosystem of IoT applications. The distributed structure of blockchain is naturally suitable for IoT applications. However, it introduces new challenges related to CPU overhead or response time. This paper proposes a layered architecture that integrates blockchain technology and OS‐level virtualization technology to develop fog‐based IoT applications. It also provides insights for future deployments through a proof‐of‐concept use case harnessing SBCs, in this case Raspberry Pi, as blockchain‐enabled fog nodes to drive virtualized IoT applications. The study shows that the maximum CPU overhead added by a permissioned blockchain based on Ethereum on the Raspberry Pi is around a 25% under stress situations while the overhead introduced by the sealer process is negligible. These results support the feasibility of using blockchain on resource‐constrained fog nodes for supporting IoT applications.